2015
DOI: 10.1007/s11102-015-0678-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic–pituitary sarcoidosis with vision loss and hypopituitarism: case series and literature review

Abstract: HP NS is a serious disease requiring multidisciplinary treatment and lifelong follow-up. Prospective multicentric studies are needed to determine a more standardized approach to HP NS and outline predictors of disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 25 publications
1
30
0
9
Order By: Relevance
“…Imaging studies are usually characterised by sellar/suprasellar masses with or without pituitary stalk thickening. Hypothalamic and pituitary sarcoid involvement appears to be more common in men as opposed to other manifestations of sarcoidosis which have a female predilection 7. Earlier postmortem studies of patients with sarcoidosis complicated by hypopituitarism assumed that the hormone deficiency was due to pituitary gland destruction by granuloma formation,8 but subsequent studies showed responsiveness of pituitary gland to synthetic hypothalamic releasing factors suggesting that hypothalamic insufficiency may be the major cause of hypopituitarism in these patients 9…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging studies are usually characterised by sellar/suprasellar masses with or without pituitary stalk thickening. Hypothalamic and pituitary sarcoid involvement appears to be more common in men as opposed to other manifestations of sarcoidosis which have a female predilection 7. Earlier postmortem studies of patients with sarcoidosis complicated by hypopituitarism assumed that the hormone deficiency was due to pituitary gland destruction by granuloma formation,8 but subsequent studies showed responsiveness of pituitary gland to synthetic hypothalamic releasing factors suggesting that hypothalamic insufficiency may be the major cause of hypopituitarism in these patients 9…”
Section: Discussionmentioning
confidence: 99%
“…Hypogonadism appears to be the most common hormone deficiency associated with hypothalamic pituitary sarcoidosis 7 10 11. In a study of nine patients with hypothalamic–pituitary sarcoidosis, hypogonadism occurred in all the patients, diabetes insipidus in seven patients and hyperprolactinaemia in three patients 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bilateral facial nerve palsy) is suggestive of NSOptic nerve involvement may have a more difficult disease course with refractory disease and relapse on corticosteroid dose reductionA pharynx, soft palate and vocal cord syndrome from glossopharyngeal and vagus nerve involvement is recognisedBasal meningitis may be the pathophysiological substrate of cranial neuropathiesFocal neurology, multifocal neurology or diffuse encephalopathy due to parenchymal lesions of the brain or brainstem [2, 8, 9, 18–22, 44]Lesions may be multiple and often enhance. Biopsy of mass lesions is recommended for a definitive diagnosisBehaviour change, confusional states and psychosis are reportedHypothamic and pituitary dysfunction [2, 6, 8, 9, 20, 22, 28, 29, 4446]Usually of insidious onset, due to suprasellar inflammatory lesions. The most eminent symptoms are bitemporal visual failure, polydipsia and polyuria (diabetes insipidus), and galactorrhoeaSymptoms may arise from hypothalamic dysfunction, hypopituitarism or compression of the optic chiasm by mass effectAn aseptic meningitis is often seenMyopathy [6, 19, 20, 22, 38]Usually asymptomatic.…”
Section: Diagnosismentioning
confidence: 99%
“…Central nervous system is affected in 5-15% of cases, and neurosarcoidosis may be the first presenting feature of these systemic diseases (57). Lesions of sarcoidosis in the sellar region are found in the hypothalamus, the stalk and pituitary gland; are rare and account for 1% of sellar masses (58). The classic MRI feature is thickening of the stalk.…”
Section: Sarcoidosismentioning
confidence: 99%